A microstructure-based fatigue model for additively manufactured Ti-6Al-4V, including the role of prior β boundaries. (April 2023) - Krishnamoorthi, Sidharth; Bandyopadhyay, Ritwik; Sangid, Michael D.
Highlights: Developed framework for synthetic microstructures of additively manufactured Ti-6Al-4V. Virtual microstructures explicitly modeled prior β boundaries and α laths features. Prior β boundaries and hard-soft α laths are likely locations of fatigue crack initiation. The inclusion of prior β boundaries resulted in a reduced mean predicted fatigue life. Microplasticity at prior β boundaries is evident at loads below the percolation limit. Abstract: Microstructure-based models of additive manufactured (AM) Ti-6Al-4V should faithfully represent the unique microstructural features of these materials to provide a more thorough understanding of their role in the mechanical performance of the material. For AM Ti-6Al-4V, the prior β boundaries are likely sites of microscopic plastic strain localization, often leading to fatigue crack initiation. Within the context of crystal plasticity finite element methods, there is an existing gap in the current literature for creating synthetic microstructures of Ti-6Al-4V that capture both the prior β boundaries and α laths. This work focuses on generating such statistically equivalent microstructures, where the prior β boundaries and α laths are explicitly modeled. The framework can generate synthetic microstructures that consider one prior β grain or multiple β grains (and thus prior β grain boundaries) and their associated α laths forming a Widmanstätten microstructure, which are used as inputs for fatigue simulations. Within the fatigue model, the critical accumulated plastic strain energy density (APSED) is a metric used to predict the location and number of cycles of crack initiation. From a statistical average perspective, the presence of prior β grain boundaries was detrimental to the fatigue performance. The effectiveness of the prior β grain boundary in impeding slip, and therefore localizing APSED, is dependent on the loading conditions, prior β orientations, and α variants present in neighboring prior β grains. A higher percentage of failures occurred at the prior β grain boundary in the case of lower applied stress amplitudes, where the applied loads were below the percolation limit of the material and microplasticity was localized to a few locations relative to the microstructure. Additionally, for the case of crack initiation associated with the α variants within a given prior β grain, a combination of soft-hard α lath orientations resulted in sites of APSED localization and predicted fatigue crack initiation. The framework generated in this paper to create representative synthetic microstructures of the Widmanstätten microstructures associated with AM Ti-6Al-4V and the associated fatigue modeling enables trade-off studies between microstructural features and fatigue performance. Graphical abstract: Image, graphical abstract